Effect of tumor microenvironment on ferroptosis: inhibition or promotion - Xia, Zhengzhen; Quan, Yi (Frontiers in Oncology, 2023)
Ferroptosis is an iron-dependent programmed cell death caused by lipid peroxidation. Emerging evidence suggests that ferroptosis is closely related to tumorigenesis, development, and treatment and plays a major role in tumor immune regulation. This study focused on the interaction between ferroptosis and immune regulation, which might provide a theoretical basis for targeting ferroptosis and tumor immunotherapy.